Women Empowerment through Quran: An Alternative Narrative to the Western Liberal Feminism (Al-Qamar, 2021)
The current narrative of Western Liberal Feminism is strongly built upon the financial independence of women. Some even call it ‘Financial Empowerment’. In fact, this is only one aspect of women empowerment. The history of Islamic world reveals that Islam initiated its own version of empowerment of women through the Holy Quran. From its inception, Islam marks it mandatory upon every member of Islamic society to seek knowledge. Since the advent of Islam till today, female Muslim scholars, from around the globe, have been consistently contributing to the realm of Islamic knowledge. Starting from Hazrat Aisha (May Allah be pleased with her) as the very first prominent female Muslim scholar till date, countless female scholars have emerged on the horizons of Islamic scholarship, making their valuable contributions to women empowerment. It is argued that throughout the Islamic history, women have shared their intellect, caliber, enthusiasm and wisdom, enriching the heritage of Islamic scholarship. Till date, one can find the examples of such empowered women in Islamic world who are contributing to shape their societies. They were not financially independent by the time when they embarked upon their respective journeys. This is to problematize here that female financial independence is only one angle of women empowerment. Islam bestows upon a novel dimension to women empowerment. This is empowerment through the Holy Qur’ān. The knowledge, wisdom and intellectualism acquired through the Qur’ān truly empowered women in Islamic history and continues to this date. Female Muslim scholars are using that intellect and wisdom and very actively shaping the course of history alongside the opposite gender - men. Dr. Farhat Nasim Hashmi is amongst one of such scholars of the contemporary Islamic world. Her services for spreading the teachings of the Holy Quran not only transcended the borders of her native country; rather it became a global wave and a positive paradigm shift in the teachings of Islam when her brainchild ‘Al-Huda International’ was founded. We posit that she is an epitome of women empowerment, and this didn’t stem from financial independency but is deeply rooted in the education of the Holy Qur’ān. Moreover, she has made countless woman empowered through intellectualization achieved through the Holy Book. The paper also examines the process of transfer of empowerment through analysis of her Islamic School System. Moreover, it includes results of an analysis of interviews conducted from women, all of which supports the view that their empowerment does not lie in being financially independent but in gaining wisdom through the Holy Quran.
Keywords: Women Empowerment; Feminism; Intellectualism; The Quran; Islam; Dawah; AL-Huda; Islamic Revivalist Movements